2022
DOI: 10.1038/s41598-022-15654-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the environment and indoor residual spraying on malaria risk in a cohort of children in Uganda

Abstract: Studies have estimated the impact of the environment on malaria incidence although few have explored the differential impact due to malaria control interventions. Therefore, the objective of the study was to evaluate the effect of indoor residual spraying (IRS) on the relationship between malaria and environment (i.e. rainfall, temperatures, humidity, and vegetation) using data from a dynamic cohort of children from three sub-counties in Uganda. Environmental variables were extracted from remote sensing source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Furthermore, the research findings indicated that environmental factors contribute to the increased malaria prevalence in the study area. A previous study by Sadoine et al ( 2022 ) and Arhin et al ( 2023 ) suggested that higher temperatures may lead to elevated malaria levels, potentially due to changes in mosquito populations. This underscores the importance of considering climate change in developing early warning systems and response strategies.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the research findings indicated that environmental factors contribute to the increased malaria prevalence in the study area. A previous study by Sadoine et al ( 2022 ) and Arhin et al ( 2023 ) suggested that higher temperatures may lead to elevated malaria levels, potentially due to changes in mosquito populations. This underscores the importance of considering climate change in developing early warning systems and response strategies.…”
Section: Discussionmentioning
confidence: 97%
“…However, the current model tuning does not consider the introduction of various vector control interventions (such as bednet use), leading to an earlier onset of malaria season as shown in Figure 11. The decline in both clinical episodes and deaths due to malaria is primarily associated with the expansion of vector‐control measures, such as insecticide‐treated bednets and indoor residual spraying (Elmardi et al., 2021; Musiime et al., 2019; Sadoine et al., 2024). While tuning model parameters, we observed a significant sensitivity of VECTRI schemes S1 and S2 to the parameter “wperm” (fraction of permanent water bodies, see Equation ), that is, setting “wperm” to 0.001 produces results that match the observed malaria cases from January to May.…”
Section: Discussionmentioning
confidence: 99%